Associations of parental attitudes and health behaviors with children's screen time over four years - Qian-Wen Xie; Roujia Chen; Xudong Zhou (BMC, 2023)
Abstract Background Parents are significantly important in shaping the screen use of children within a family system. This study aimed to examine the associations of Chinese children's screen time (ST) over four years with parents' attitudes toward their own screen use and physical activities (PA) and health behaviors including their ST, PA, cigarette smoking, and alcohol drinking. Methods The current study utilized data from two waves (2011 and 2015) of the China Health and Nutrition Survey (CHNS), including 1,941 mother-father-child triads in 2011 and 2,707 mother-father-child triads in 2015 (with children aged 0-17-years-old). The ST of children and the parental attitudes and health behaviors were measured via self-report or proxy-report (for children under 6 years old) questionnaires. Pool-OLS regression models were used to assess the associations of parental attitudes and health behaviors with the ST of children. Moderation models were built to assess whether these associations depended on the gender, age, and family income of children, as well as whether paternal and maternal influences were moderated by the other parent. A multilevel cross-lagged panel model (CLPM) was used to assess parental influences on children's ST over four years. Results Paternal ST (β = 0.09, p < 0.001), maternal ST (β = 0.10, p < 0.001), and paternal alcohol drinking (β = 0.30, p < 0.05) were positively associated with children's ST. In addition, maternal smoking had a positive association with girls' ST (β = 0.53, p < 0.05). Moreover, the association between maternal ST and children's ST was observed to decline as family income increased (β = -0.03, p < 0.001). Paternal ST had a larger positive association with children's ST when the ST of mothers exceeded 14 h/week (β = 0.06, p < 0.05). Furthermore, lagged associations were found between paternal attitudes toward PA (β = -1.63, p < 0.05) or maternal cigarette smoking (β = 1.46, p < 0.05) and children's ST measured four years later. Conclusion Children establish a healthy lifestyle within the family system. From the perspective of the healthy family climate, the current study suggests that future programs for reducing children's ST should be built through an integrative approach with special attention to parental attitudes and health behaviors.